Cambridge International AS and A level Chemistry Coursebook - Norris, Roger ; Ryan, Lawrie and Acaster, David (New York Cambridge University Press, 2012)
Cambridge International AS and A Level Chemistry is tailor-made to comprehensively cover Cambridge syllabus requirements. Written by highly experienced authors and Cambridge examiners, this book offers full support to students. Simple and clear language, colourful photos and international examples make this book accessible to students from around the world. Exam-style questions at the end of each chapter reinforce knowledge and skills and offer thorough exam practice.
Include Color Illustrations and Index
Keywords: Chemistry -- A-level examinations -- Advanced supplementary examinations -- Chemistry--Examinations